Abacus of loss : a memoir in verse - Wolpé, Sholeh (Book collections on Project MUSE., 2022)
"In Sholeh Wolpé's memoir in verse, the poet wields an abacus as an instrument of remembering. Bead by bead, she takes the reader on a journey of love and exile, loss and triumph"--